A construção do ethos masculino em anúncios publicitários de perfume à luz de uma análise semiolinguística - Lopes, Lucineide Matos (2020)
Studies on ethos go back to ancient rhetoric, being taken up and redefined in more recent works such as in Argumentation Analysis, in Amossy (2013); in Critical Discourse Analysis, at Fairclough (2008); in French Discourse Analysis, in Maingueneau (2013); in Semiolinguistic Theory, in Charaudeau (2013b). We are involved in this last perspective, because the ethos starts in the language subject, being made of discourse and being social, which allows a broad reflection on the process of subjects adhering to the discourse. Our research aims to analyze the construction of the male ethos considering the set of ethé that emerges from the language act, the discursive, imagetic and social effects, projected by the body image, in perfume advertisements. From a theoretical point of view, we are anchored in the assumptions of Charaudeau's Semiolinguistic theory (2001; 2004; 2005; 2009a; 2009b; 2010a; 2010b; 2010c; 2011; 2013a; 2013b; 2013c; 2017). Charaudeau (2004; 2005; 2010c; 2011) to highlight the conceptions of language, language, speech, text, context, gender; Charaudeau (2009a; 2009b; 2010b) to investigate advertising discourse. Thus, we present as an assumption that the construction of the male ethos occurs from the set of ethé that emerges in the advertising scene, due to the relationship between the subjects of the staging and the social and discursive identities, due to the effects targeted and produced in the production and perception processes of photographic image, and by the manifestation of sociodiscursive imaginary. From the methodological point of view, we conducted an inductive investigation of the analytical-discursive type through the interpretation of thirty advertisement of perfume. At first, to characterize the set of ethé that emerges in the advertisement, we used the following categories: ethos of credibility and ethos of identification (CHARAUDEAU, 2013a; 2013b). In the second moment, to analyze the discursive effects, we use the categories of subjects in the staging (CHARAUDEAU, 2001; 2010a), and the social and discursive identities (CHARAUDEAU, 2009a 2013c) In the third moment, to investigate the imagetic effects, we use the categories of targeted effects and produced effects (CHARAUDEAU, 2013c). In the fourth moment, to examine the social effects, we use the sociodiscursive imaginary (CHARAUDEAU, 2013b; 2017). As a result, we observe that the set of ethé that emerges in the advertisement is characterized as ethos of identification; the category of the credibility ethos is also constructed by the image of the model that makes up the ad. Regarding the discursive dimension, the subjects of the advertising scene are recognized in connection with the male ethos; the enunciating subject understands the images of the models associated with the dream proposals, and these proposals resemble the identified ethé; the credibility and capture strategies are verified in the construction of the enunciating subject's discursive identity. As for the imagery dimension, the effects of focusing, dramatization, sideration and studium are recurrent, and in relation to the set of ethé that emerges in the advertisements in order to reinforce their power of seduction. In the social dimension, we determine the sociodiscursive imaginary materialized in advertising texts. As a conclusion, we found that the discursive, imagetic and social effects are relevant strategies in the construction of the masculine ethos, to reinforce more and more the incitement to the consumption of advertising discourse, in perfume advertisements.